Quantitative study of the hardening in the Alpha Magnetic Spectrometer nuclei spectra at a few hundred GV - Niu, Jia-Shu; Liu, Jing (Frontiers in Astronomy and Space Sciences, 2022)
The most significant feature in the cosmic-ray (CR) nuclei spectra is the spectral hardening at a few hundred GV. Whether the hardening of the different nuclei species are same or not is important for constructing CR source and propagation models. In this work, we collect the latest released AMS-02 CR nuclei spectra of primary species (proton, helium, carbon, oxygen, neon, magnesium, silicon, and iron), secondary species (lithium, beryllium, boron, and fluorine), and hybrid species (nitrogen, sodium, and aluminum), and study the break positions and the spectral index differences (less and greater than the break rigidity) of the spectral hardening quantitatively. The results show us that the CR nuclei spectral hardening at a few hundred GV has hybrid origins. In detail, the dominating factors of the spectral hardening for primary and secondary CR nuclei species are different: the former comes from the superposition of different kinds of CR sources, while the latter comes from the propagation process. Both of these factors influence all kinds of CR nuclei spectra, just with different weights.